ТРИВАЛЕ СПОСТЕРЕЖЕННЯ ВЕЛЕТЕНСЬКОЇ НУЛЬ-КЛІТИННОЇ АДЕНОМИ ГІПОФІЗА - UKRAINETS, O.; GUK, M.; DANEVYCH, O.; CHUKOV, A.; MUMLIEV, A.; SOLOVEY, M.; EGOROVA, K.; TEVZADZE, D.; NABOICHENKO, A. (PH Akademperiodyka, 2024)
Pituitary adenomas that extend to the ventricular system are extremely rare. We present a 5-year natural history of a giant null cell pituitary adenoma with invasion into the cavernous sinus extending to the third ventricle. MRI series that were available could be useful for neurosurgeons, ophthalmologists, and endocrinologists as well as radiologists. Patients with the diagnosis of pituitary adenoma that are certain according to the radiological and clinical examination should be consulted by a neurosurgeon experienced in endoscopic endonasal surgery, a neuroendocrinologist, and an ophthalmologist. The surgery postponement in such cases results in disability and quality of life worsening. At that time, the surgery of giant pituitary adenomas demands high skills, and the risk of postoperative complications is high. The proper treatment modality including earlier surgery seems to be favorable for patient outcome.